Effects of Couple Stress on the Growth Rate of Rayleigh- Taylor Instability at the Interface in a Finite Thickness Couple Stress Fluid - N. Rudraiah (Journal of Applied Fluid Mechanics, 2010)
In this paper the effects of couple stress fluid on the control of Rayleigh-Taylor instability at the interface between a dense fluid accelerated by a lighter fluid is studied. A simple theory, based on fully developed approximations, is used to derive the growth rate of Rayleigh-Taylor instability. The cutoff and maximum wave numbers and the corresponding maximum frequency are obtained. It is shown that the effect of couple stress parameter reduces the growth rate considerably compare to the classical growth rate in the absence of couple-stress and hence favorable to control the growth rate of surface instabilities in many practical problems.